SCREENING AND RISK ASSESSMENT FOR DEPRESSION IN COMMUNITY PHARMACY- PILOT STUDY - Antonia Kondova; Anna Todorova; Antoaneta Tsvetkova; Mariana Arnaoudova; Kalina Andreevska; Daniela Grekova (Peytchinski Publishing, 2018)
Background: Depression is the most common mental illness affecting more than 300 million people worldwide and is a significant risk factor for morbidity and mortality. In most cases, it may remain undetected in primary care. Comprehensive screening tools for diagnosing depression might facilitate early detection. As the most accessible health professionals, pharmacists can play an important role in helping to identify individuals at risk. Objective: To differentiate individuals at risk of depression who are seeking a pharmacist consultation and are promptly directed to a psychiatrist. Methods: Depression screening tools The Patient Health Questionnaire (PHQ-2) and (PHQ-9) were applied to 83 individuals with symptoms such as feeling down, tiredness and sleep disturbances for more than 2 weeks, who seek consultation at a pharmacy. Screening with the PHQ-2 was the first step. Patients who screen positive were further evaluated with the PHQ-9. Results: In 70% of the individuals, the PHQ-2 test was positive. After completing PHQ-9, it was found that approximately 55% out of them had indications of mild to moderate depression and were directed to a psychiatrist for further evaluation. Over 50% of suspected depressive individuals had a concomitant chronic disease. Conclusion: Screening for depression should be a routine part of healthcare. Particular attention should be paid to patients with comorbid chronic illnesses, as depression often remains hidden, thus leading to more difficult diagnosis and treatment. Screening would also increase the recognition of depression in patients who have few emotional symptoms but many somatic ones.